Associação do consumo dietético com a sarcopenia e seus componentes em indivíduos que realizaram transplante renal - Reis, Aline Silva dos (2022)
Introduction: The loss of muscle mass and physical function (strength and functional capacity), known as sarcopenia, is prevalent in adult and older adults kidney transplant patients. This clinical condition is associated with a worse prognosis and greater risk of morbidity and mortality, in addition to making it difficult to carry out activities of daily living. On the other hand, insufficient consumption of energy and nutrients can contribute to the development of sarcopenia. In this sense, it is essential to investigate which nutrients may be associated with protection for this clinical condition in this population. Aim: To evaluate the association between dietary intake and sarcopenia and its components in kidney transplant patients. Material and Methods: A crosssectional study was performed at a clinical hospital of the Federal University of Uberlandia, Minas Gerais, Brazil; evaluating kidney transplant patients (KTPs) at the kidney transplantation ambulatory clinic. Dietary assessment was performed using two 24-hour dietary recalls, using the five steps multiple-pass method. The assessment of body composition was performed using bioimpedance. Appendicular skeletal muscle mass was estimated using the equation by Sergi et al. (2015). The appendicular skeletal muscle mass index was calculated, which consists of the appendicular skeletal muscle mass (kg) divided by the height squared (m²). The handgrip strength test (HGS) and five times sit to stand test (5STS) were performed to assess muscle strength. Functional capacity was assessed using the short physical performance battery (SPPB) and the 4-m walking test. Sarcopenia was diagnosed using the criteria proposed by the Revised European Consensus on Sarcopenia. Several statistical models were performed to verify the association between dietary variables and prevalence of sarcopenia, muscle mass, muscle strength and functional capacity of the participants. Results: In the first article, it was shown that omega-3 fatty acid intake was positively associated with appendicular skeletal muscle mass index and higher intake of polyunsaturated and omega-3 fatty acids was associated with a lower chance of having low muscle mass index skeletal and sarcopenia in total sample. In the second article, it was observed that the number of meals containing at least 30 grams of protein was negatively associated with the time to perform 5STS and positively associated with the SPPB score among KTPs aged 50 years or more, regardless of confounding factors. Conclusions: Intake of omega-3 fatty acids and polyunsaturated fatty acids are protective factors for sarcopenia and low muscle mass, but not for strength and functional capacity, in KTPS. Additionally, the number of meals containing at least 30 grams of protein is associated with better performance on 5STS and SPPB in KTPs aged 50 years and over. Future randomized controlled trials should be performed to assess the effect of these nutrients on sarcopenia and its components in KTPs.